Entrepreneurship Psychological Characteristics of Nurses - Mohammad Reza Dehghanzadeh; Golrasteh Kholasehzadeh; Masoumeh Birjandi; Ensieh Antikchi; Mohamad Reza Sobhan; Hossein Neamatzadeh (Acta Medica Iranica, 2016)
Nurses are full partners with other health care professionals. Until fairly recently the scope of nurses potential in entrepreneurship has not been widely recognized. The present study tries to evaluate entrepreneurship psychological characteristics among nurses. The survey instrument included scales measuring entrepreneurship psychological characteristics including locus of control, need for achievement, risk taking propensity, ambiguity tolerance, and innovation, among nurses in the Shahid Sadoughi Hospital, Yazd, Iran in 2013. In this study average of entrepreneurship psychological characteristics of nurses which are higher than standard mark. The majority of the nurses have average entrepreneurship (20.4%). It means that they have some strong entrepreneurship. The result show that average of the need for achievement is 34.5%, the locus of control 33.8%, risk taking propensity 33.2%, ambiguity tolerance 34.2%, and innovation 41.6%. The results indicate that the 4 dimensions of the need for achievement, risk taking, Ambiguity Tolerance, and Innovation were significant. However, the locus of control is not significant at a 0.05 significance level. In terms, entrepreneurially nurses are comparatively more innovative, have risk taking attitudes, need for achievement, Ambiguity Tolerance, and Innovation. Results largely support significant positive relationships between psychological traits and entrepreneurial orientations.